PTX3 Regulation of Inflammation, Hemostatic Response, Tissue Repair, and Resolution of Fibrosis Favors a Role in Limiting Idiopathic Pulmonary Fibrosis - Doni, Andrea; Mantovani, Alberto; Bottazzi, Barbara; Russo, Remo Castro (Frontiers in Immunology, 2021)
Abstract: PTX3 is a soluble pattern recognition molecule (PRM) belonging to the humoral innate immune system, rapidly produced at inflammatory sites by phagocytes and stromal cells in response to infection or tissue injury. PTX3 interacts with microbial moieties and selected pathogens, with molecules of the complement and hemostatic systems, and with extracellular matrix (ECM) components. In wound sites, PTX3 interacts with fibrin and plasminogen and favors a timely removal of fibrin-rich ECM for an efficient tissue repair. Idiopathic Pulmonary Fibrosis (IPF) is a chronic and progressive interstitial lung disease of unknown origin, associated with excessive ECM deposition affecting tissue architecture, with irreversible loss of lung function and impact on the patient’s life quality. Maccarinelli et al. recently demonstrated a protective role of PTX3 using the bleomycin (BLM)-induced experimental model of lung fibrosis, in line with the reported role of PTX3 in tissue repair. However, the mechanisms and therapeutic potential of PTX3 in IPF remained to be investigated. Herein, we provide new insights on the possible role of PTX3 in the development of IPF and BLM-induced lung fibrosis. In mice, PTX3-deficiency was associated with worsening of the disease and with impaired fibrin removal and subsequently increased collagen deposition. In IPF patients, microarray data indicated a down-regulation of PTX3 expression, thus suggesting a potential rational underlying the development of disease. Therefore, we provide new insights for considering PTX3 as a possible target molecule underlying therapeutic intervention in IPF.